Putting Inuinnait place names on the map - Collignon, Béatrice (HAL CCSD, 2005)
Film documentaire en langue anglaise (et quelques dialogues en inuktitut). Tournage et montage de l'auteur. Durée : 15' Atelier Géo-vidéo de l'Université de Paris 1 This document is a video documentary that recounts the various phases of the collection and official recognition of a set of Inuit place names in the Canadian Arctic.